Gender Education in Disruption Era (Study Of Virtual Ethnography) - Sudirman Sudirman; Rosramadhana Rosramadhana; Ayu Febryani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Education is an academic level without being restricted to gender. Men and women are basically entitled to education. Education for men and women should get the same treatment. Education will continue to experience a complicated phase but will give birth to an established generation in technology. But the challenge of facing the speed of technology will change the way humans work in obtaining education. Education for men and women in the disrupted era has different challenges, but addressing the problems that arise today women will have an impact if the preparation for the era of disruption is not protected by the government. Avoiding participation in the practice of cyber bullying and cybercrime is another form of protection in understanding and responding to this era wisely and wisely. The virtual ethnographic approach is the cornerstone of the strategy to see the development of education for men and women with a model of technology-friendly education to answer the challenges of education in the era of disruption.